SNARE proteins SYP22 and VAMP727 negatively regulate plant defense. (3rd July 2019) - Zhu, Xiao Feng; Liu, Yang; Gai, Xiao Tong; Zhou, Yuan; Xia, Zhen Yuan; Chen, Li Jie; Duan, Yu Xi; Xuan, Yuan Hu
ABSTRACT: Soluble N-ethylmaleimide sensitive factor attachment protein receptors (SNAREs) are the key regulators control trafficking of cargo proteins to their final destinations and plays key role in plant development; however, their roles in plant defense remain largely unknown. R-SNARE VAMP727 and Qa-SNARE SYP22 were previously reported to associate with vacuolar protein deposition and brassinosteroids (BRs) receptor BRI1 plasma membrane targeting. Here, we identified that VAMP727 and SYP22 are induced by infection of root-knot nematode (RKN), a plant pathogen, which cause severe growth defect and yield loss. Furthermore, decreased root-knot nematode (RKN) invasion, growth and disease index were observed in bri1-5 and SYP22ND, a SYP22 negative dominant mutants when compared to control plants. Overall, our results suggest that VAMP727-SYP22 SNARE complexes regulate plant defense might be via control of abundances of BRI1 on the plasma membrane.